Using Ambient Ion Beams to Write Nanostructured Patterns for Surface Enhanced Raman Spectroscopy1. (3rd September 2014) - Li, Anyin; Baird, Zane; Bag, Soumabha; Sarkar, Depanjan; Prabhath, Anupama; Pradeep, Thalappil; Cooks, R. Graham
Abstract Electrolytic spray deposition was used to pattern surfaces with 2D metallic nanostructures. Spots that contain silver nanoparticles (AgNP) were created by landing solvated silver ions at desired locations using electrically floated masks to focus the metal ions to an area as little as 20 μm in diameter. The AgNPs formed are unprotected and their aggregates can be used for surface‐enhanced Raman spectroscopy (SERS). The morphology and SERS activity of the NP structures were controlled by the surface coverage of landed silver ions. The NP structures created could be used as substrates onto which SERS samples were deposited or prepared directly on top of predeposited samples of interest. The evenly distributed hot spots in the micron‐sized aggregates had an average SERS enhancement factor of 108. The surfaces showed SERS activity when using lasers of different wavelengths (532, 633, and 785 nm) and were stable in air.